Enhancement of the thermal performance of an evacuated tube solar collector using nanofluids with grapheme nanoplatelets / Soudeh Iranmanesh - Soudeh , Iranmanesh (2019)
Solar thermal energy can be a good replacement for fossil fuel because it is clean and sustainable. However, the current solar technology is still not efficient. This research is carried out experimentally and analytically to investigate the thermal performance of evacuated tube solar collector (ETSC) using graphene nanoplatelets (GNP) nanofluid as working fluid. Therefore, in order to achieve the desired thermal conductivity and viscosity; experimental and statistical approaches were combined by selecting the best concentration, temperature, proper surface area and type of base fluid. In the first stage of this study, three influential parameters on the viscosity and thermal conductivity including concentration, temperature and specific surface area of GNP were investigated. A mathematical model was developed by response surface methodology (RSM) based on a central composite design (CCD). In addition, the significance of the models was tested using the analysis of variance (ANOVA). The optimum results of GNP nanofluid showed that the concentration has a direct effect on the relative viscosity and thermal conductivity. Furthermore, predicted responses proposed by the Design Expert software were compared with the experimental results. The statistical analysis of the predicted values was in satisfactory agreement with the empirical data. In the second stage, the effect of GNP/distilled water nanofluid on the thermal performance of evacuated tube solar collector (ETSC) was investigated. The mass percentage of GNP considered was 0.025, 0.05, 0.075 and 0.1 wt%. The thermal efficiency tests on the solar collector were carried out for varying a volumetric flow rate of 0.5, 0.1, and 1.5 L/min following the ASHRAE standard 93E2003. The results indicated that the solar collector thermal efficiency gave the enhancement up to 90.7% at a flow rate of 1.5 L/min when the GNP nanofluid 0.1 wt% was used as an absorption medium. The results indicated that by increasing the mass percentage of nanoparticles, thermal energy gain also increases, reaching a higher outlet temperature of the fluid when graphene nanoplatelets are used. In addition, the thermodynamic performance of the cycle for the second law analysis also investigated. For this purpose, the experimental data on the performance of set-up is used to estimate the exergy efficiency and destruction, entropy generation, Bejan number and pumping power. The results showed that the exergy efficiency was enhanced with particle concentration and simultaneously decrease with mass flow rate. It also found that the entropy generation reduced with increasing the nanofluid concentration. The Bejan number surge up with increasing the concentration while this number decreases with enhancement the mass flow rate. In the last stage, Numerical simulation was carried out using 3-dimensional computational fluid dynamic (CFD) to confirm the results for outlet temperature at 0.5 L/min. Comparison of the simulation results with the experimental data reveals that the model could predict the outlet nanofluid temperatures within a maximum relative error of 9.4% and mass flow rate were found in reasonable agreement with the available experimental outcome. Keywords: